Pengembangan Kompetensi Mahasiswa PAK Menyusun Perangkat Pembelajaran Kurikulum Merdeka Melalui Workshop - Muara, Taurus Ida; Fianus Tandiongan; Chandra Kirana Luhur (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
Teacher competence is a composite of knowledge, skills, attitudes, motivation, and personal characteristics that enable educators to perform effectively in their professional roles. Students of Christian Religious Education (CRE) can study curriculum content based on the Merdeka Curriculum through workshops. This study employs a mixed-methods approach, combining quantitative and qualitative methodologies, using a one-level Research and Development (R&D) design. The research and development process is oriented toward product development—specifically, learning materials based on the Merdeka Curriculum delivered through workshops. A total of 10 validators and respondents provided positive feedback. The content of the developed product is deemed appropriate for assessing the competence development of Christian Religious Education students at STT Alfa Omega.